Impact of COVID-19 pandemic on postgraduate medical education – a survey of UK trainees. (2021) - Ehilawa, Patience; Thompson, Fiona; Ahmed, Rana; Ariyo, Mary; Muldoon, Sarah; Sadler, Paul; Corne, Jonathan
No abstract available